ANALISIS WACANA KRITIS PADA HIKAYAT SI MISKIN DAN HIKAYAT INDERA BANGSAWAN DALAM BUKU TEKS BAHASA INDONESIA DI KELAS X SMA NEGERI 2 KABUPATEN BURU - Musyawir, Musyawir; Nurmina Labalawa; Darna Umagapi (Bajang Institute, 2024)
This study aims to describe the form of text structure, social context, and social cognition of critical discourse in the folklore of “the poor” and “Sense of the Aristocracy”. The research approach used in this research is qualitative. Meanwhile, the type of research used in this study is the study of documents or texts. The research data is in the form of written data in the form of sentences containing text structure, social cognition, and social context in folklore (hikayat) in class X Indonesian language textbooks. The source of data in this study is folklore in class X Indonesian Language and Literature textbooks. X by Suherli, et al. published by the 2017 revised edition of the Ministry of Culture and Education. The data collection technique in this study used library research. Meanwhile, data analysis techniques in this study are processing data and preparing data for analysis, reading all the data, analyzing in more detail by coding the data, applying the coding process to describe themes, showing how these descriptions and themes will be written. in the narrative or qualitative report and finally the interpretation of the data. The results of the study show that the microstructure discusses the elements of the saga of the poor, namely having a setting, details, and intentions that are easy for readers to understand. The author also uses sentence forms and pronouns in accordance with Indonesian Spelling (EBI). Another element in the micro structure is stylistics or figurative language. Complete with the choice of words, sentence forms, and metaphors that use or use many archaic words. In terms of social cognition, the communicator, in this case the author of the novel, seems to want to give a moral message about never giving up, no matter what path of life is given by Allah SWT. In terms of the social context, the writer concludes that this novel was created as an idea that becomes the author's message or message to the reader, which is about never giving up.